Recent advances in the multifaceted mechanisms of catalpol in treating osteoporosis - Li, Na; Mu, Xiaoying; Zhang, Shudong; Wang, Huaxin (Frontiers in Pharmacology, 2025)
Catalpol (CAT) is a landmark active ingredient in traditional Chinese medicine Rehmannia (TCT), also known as dehydroxybenzoate catalpone, which is a kind of iridoid terpene glycoside with strong antioxidant, anti-inflammatory, antitumor and other biological activities. It can exert its anti-disease effect in a variety of ways. For some patients with chronic diseases, the application of azalea alcohol in rehmannia may bring more comprehensive and long-lasting efficacy. Studies have shown that the anti-disease effect of catalpol in osteoporosis (OP) is mainly achieved through various pathways such as Wnt/β-catenin signaling pathways to promote osteogenic differentiation, and RANKL/RANK and other signaling pathways to inhibit osteoclastic differentiation. At present, there is a slight lack of analysis of the mechanism of action of catalpa alcohol in the treatment of osteoporosis, so this study comprehensively searched the literature on the mechanism of action of catalpa alcohol in the treatment of osteoporosis in various databases, and reviewed the research progress of its role and mechanism, to provide reference and theoretical basis for the further development and application of catalpol.